Rooftop solar capacity modeling using GIS within the city of Stillwater, MN - Brandt, David (My University, 2014)
Solar power has long been looked to as a source of renewable power. Expensive and inefficient solar materials and methods have become more attractive as technology and costs have improved. Coupled with an aging and deteriorating energy grid and increasing fossil fuel prices, the future of solar power is a promising alternative. As more homeowners and businesses investigate the feasibility of small scale photovoltaic solar installations, more accurate methods for predicting solar capacity are necessary. The purpose of this study was to analyze the total rooftop solar capacity within the city of Stillwater. This study utilized light radar (LiDAR) data and Geographic Information System (GIS) technology to analyze rooftop solar capacity for residential and commercial properties within the city of Stillwater, MN. The use of LiDAR data is preferred to previously available digital elevation data due to a higher precision and ability to identify trees and buildings. The research was conducted by creating a digital terrain dataset that takes into account the shadows from trees and buildings. The terrain model was also used to calculate roof slope and aspect to identify optimum rooftop location for installation of photovoltaic solar cells. With the total solar insolation calculated, structures were analyzed for viability of roof mounted solar power. Although this study focused on residential properties, commercial properties showed higher insolation values. Older residential structures proved to be better candidates than originally thought. In part due to their east-west orientation, size, height and roof angle. Also, there has been some loss of large, mature trees that may have affected shading. These favorable results may impact future planning and zoning decisions in the historic areas of Stillwater. While a number of homes in the newest residential areas have high potential, they also have fewer mature trees which may greatly affect future solar potential. Also, the curvilinear nature of the roads in these neighborhoods negatively affects solar potential for many properties due to house orientation. Nearly half of all residential properties within the city of Stillwater were found to have the potential to offset at least half their energy usage through solar power.
Thesis (M.S.)--University of Wisconsin-River Falls, 2014. vii + 466 leaves. Includes bibliographical references (leaves 42-44).
Keywords: Solar energy--Minnesota--Stillwater--Analysis; Energy conservation--Minnesota--Stillwater--Analysis; Renewable energy sources--Minnesota--Stillwater--Analysis; Dwellings--Energy conservation--Minnesota--Stillwater